ENERGY EVALUATION OF HYBRID COLLECTOR FAÇADE USING MITHRA SOFTWARE - A.P., Evan,; R.C., Moore (JoDA Journal of Digital Architecture, 2025)
The growing demand for building energy efficiency has driven the development of active façade systems that harness solar energy. This study aims to evaluate the performance of a hybrid solar façade collector that utilizes two types of fluids—air and solar fluid—to enhance primary energy efficiency. The method employed is numerical simulation using the specifically developed MITHRA software, based on two-dimensional finite difference modeling and climate data from DWD. Validation was conducted through experiments using four test collector units. A matched-flow control strategy was implemented to optimize system operation based on actual energy efficiency. The results indicate that the use of dual fluids does not always outperform single-fluid systems; however, system efficiency improved significantly—by up to 15%—when the control strategy was applied. The MITHRA software also proved effective as a planning tool for the design of solar energy-based building façades.